EFEKTIFITAS APLIKASI UJIAN ONLINE PADA SMP NEGERI 20 KOTA JAMBI: Online Exam, effectiveness, UNBK - Rini, Faiza; Satria Nugraha, Raka (LP2M Universitas Nurdin Hamzah, 2019)
This study discusses how the effectiveness of the Online Exam Application at SMP Negeri 20 Jambi City. At present the results of student grades based on computer-based national exam results (UNBK) at SMP Negeri 20 Jambi City have not yet achieved good test scores or have not met the minimum score criteria. With the online exam application, it can provide results and positive responses especially to students. And with this application the average results of students' readiness in facing online exams can increase by an average of 95% and this is a pretty good result. the effectiveness can be seen from the teacher and student data that 10 teachers and 97 students stated that the online exam application was effective in preparing students for UNBK. This application uses PHP, MSQL, cPanel, and Xampp tools. The output of this research can be in the form of online exam system software products.